2013
DOI: 10.1186/1297-9716-44-86
|View full text |Cite
|
Sign up to set email alerts
|

Camel Streptococcus agalactiae populations are associated with specific disease complexes and acquired the tetracycline resistance gene tetM via a Tn916-like element

Abstract: Camels are the most valuable livestock species in the Horn of Africa and play a pivotal role in the nutritional sustainability for millions of people. Their health status is therefore of utmost importance for the people living in this region. Streptococcus agalactiae, a Group B Streptococcus (GBS), is an important camel pathogen. Here we present the first epidemiological study based on genetic and phenotypic data from African camel derived GBS. Ninety-two GBS were characterized using multilocus sequence typing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 30 publications
3
44
0
Order By: Relevance
“…detected 36% (37/92) TET resistance in S. agalactiae isolates from camel wound infections and mastitis that was mainly mediated by a Tn 916 ‐borne tet (M). ST616 ( n = 22) was the major resistant clone, followed by ST612 and ST617 …”
Section: Resultsmentioning
confidence: 99%
“…detected 36% (37/92) TET resistance in S. agalactiae isolates from camel wound infections and mastitis that was mainly mediated by a Tn 916 ‐borne tet (M). ST616 ( n = 22) was the major resistant clone, followed by ST612 and ST617 …”
Section: Resultsmentioning
confidence: 99%
“…To date, only serotypes Ia, Ib and III have been previously reported in fish (Vandamme et al, 1997;Evans et al, 2008;Suanyuk et al, 2008;Suwannasang et al, 2014). GBS is an emerging zoonotic agent isolated from piscine, dolphin, bovine, crocodile, camel and human sources (Ip et al, 2006;Bishop et al, 2007;Evans et al, 2008;Fischer et al, 2013). Multilocus sequence typing (MLST) of some GBS isolates from fish in Asia, including Thailand, indicated that these belong to sequence type (ST)-7/serotype Ia and ST-283/serosubtype III-4, which are associated with invasive disease of humans in Asia (Evans et al, 2008;Delannoy et al, 2013;Kayansamruaj et al, 2014).…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…Of these 17 GBS isolates, 15 GBS isolates from Songkhla, Samut Prakan, Phetchaburi and Phatthalung provinces belong to serotype III, and two GBS from Suphanburi and Nakhon Si Thammarat provinces belong to serotype Ia (Table 1). Tetracyclineresistant GBS has been reported in several organisms, including those of piscine (Geng et al, 2012), bovine (Dogan et al, 2005;Jain et al, 2012), camel (Fischer et al, 2013) and human (Boswihi et al, 2012;Dogan et al, 2005) origin. Oxytetracycline, a member of the tetracycline group produced by Streptomyces rimosus, is permitted to be used in Thai aquaculture (Baoprasertkul et al, 2012).…”
Section: Gulf Of Thailandmentioning
confidence: 99%
See 1 more Smart Citation
“…Streptococcus agalactiae and Staphylococcus aureus have been documented as the two most important mastitis pathogens in camels. Many different bacteria have been isolated from mastitic mammary glands in camels either in the form of pure or mixed infection [29,30,8] There are various studies which have been conducted worldwide on the isolation and identification of bacterial organisms in mastitic camel milk and their effect on quantity and quality of milk. Acute or chronic mastitis is one of the important diseases of she-camel in Eastern Sudan.…”
Section: Causes Of Camel Mastitismentioning
confidence: 99%